Outcome Following the Treatment of Ventriculitis Caused by Multi/Extensive Drug Resistance Gram Negative Bacilli; Acinetobacter baumannii and Klebsiella pneumonia - Pandey, Sajan; Li, Lei; Deng, Xian Yu; Cui, Da Ming; Gao, Liang (Frontiers in Neurology, 2019)
Introduction CNS ventriculitis is a serious complication following an intracranial insult demanding an immediate treatment with a broad-spectrum antibiotic in a critical care setting. Infections due to multi/extensive drug resistance (MDR/XDR) microorganisms are very challenging which might necessitate additional approach to the ongoing practice; Intravenous and intraventricular administration of antibiotics. Aim To study the efficacy and safety of through ventricular irrigation followed by daily intraventricular antibiotic administration in patients with MDR/XDR ventriculitis. Material and method A retrospective analysis of 19 patients admitted with ventriculitis due to Acinetobacter Baumannii (AB) or Klebsiella Pneumonia (KP) at Shanghai Tenth People’s Hospital from January 2016 to October 2017 was done. Here we reviewed our experience; role of thorough ventricular irrigation with Colistin mixed normal saline followed by intraventricular Colistin therapy. Treatment outcome was evaluated based on the clinical symptoms, Cerebro-Spinal Fluid (CSF) culture, laboratory findings and complication. Results Total 19 patients were included 15 males and 4 females, mean age was 51 years which ranged from 18 to 67 years old. 14 patients had infection due to Acinetobacter Baumannii (AB) and 5 were due to Klebsiella Pneumoniae (KP). Average CSF sterilization period following ventricular irrigation and intraventricular Colistin was 6 days. 16 (84%) patients were cured and 3 (15%) died during the course of the treatment. Conclusion: In addition of Intraventricular Colistin, thorough ventricular irrigation could increase the cure rate up to 84% in patients suffering from MDR/XDR CNS ventriculitis.